Further Results on the Drazin Inverse of Tensors via Einstein Product (Communications in Mathematical Research, 2022)
In this paper, we give further results on the Drazin inverse of tensorsvia the Einstein product. We give a limit formula for the Drazin inverse oftensors. By using this formula, the representations for the Drazin inverse ofseveral block tensor are obtained. Further, we give the Drazin inverse of thesum of two tensors based on the representation for the Drazin inverse of a blocktensor.